PEDAGOGICAL CONTENT KNOWLEDGE (PCK) PROFILES OF SENIOR SECONDARY BIOLOGY TEACHERS AT PUBLIC SCHOOLS IN BIREUEN DISTRICT ACEH INDONESIA - Hasanuddin Hasanuddin; Khairil Khairil; Putri Putri; Marlina marlina (Universitas Islam Negeri Ar-Raniry, 2022)
The combination of pedagogical competence and good professional competence becomes a necessity for teachers. PCK is a knowledge developed by teachers over time, through experiences on how to teach the material in various techniques and approaches to gain a wealth of student understanding. This research was conducted to find out the profile of PCK of Biology teachers of senior high schools. The study was conducted in April 2018. The population in this study was all Biology teachers of senior high schools in Bireuen district (N=137). While the samples of this study were 32 Biology teachers selected by cluster sampling. The method used in this research was the quantitative method with descriptive analysis through survey design. Teachers’ PCK was obtained by CoRe (Content Representation) instrument and triangulated data with students’ questionnaire. The results showed that PCK profile of Biology teachers at senior high schools in Bireuen district was at the growing PCK level.